Analysis of the effect of high intensity intermittent training for young athletes - Yin, X.; Ma, X.; Zhao, Y.; Liu, K. (Revista Brasileira de Medicina do Esporte, 2023)
Introduction The CPC Central Committee and the State Council have pointed out that currently, the basic indicators of young students` physical health have completely declined. This circumstance has made adolescent physical health and improving the quality of young athletes a key issue in physical education targeting adolescents. Objective Investigate the effect of high-intensity intermittent training on young athletes. Methods 24 adolescents performed 10 intermittent high-intensity training for one month, and all athletes` pre and post-training indexes were collected and compared. Results The physical examination results of male and female athletes improved to some extent (athletes` blood pressure fluctuated during the 10 training sessions, increasing slightly, and heart rate variability increased considerably (P < 0.05). Conclusion High-intensity intermittent training has a good effect on health promotion in young athletes, and can effectively improve their physical function and competitive performance. Physical education teachers and student-athletes should conduct relevant training. In addition, this training method also fits the current learning life situation of high school students.